Biphasic modulation of parallel fibre synaptic transmission by co‐activation of presynaptic GABA(A) and GABA(B) receptors in mice - Howell, Rebecca D. (J Physiol, 2016)
KEY POINTS: Many excitatory synapses co‐express presynaptic GABA(A) and GABA(B) receptors, despite their opposing actions on synaptic transmission. It is still unclear how co‐activation of these receptors modulates synapse function. We measured presynaptic GABA receptor function at parallel fibre synapses onto stellate cells in the cerebellum using whole‐cell patch‐clamp recording and photolytic uncaging of RuBi‐GABA. Activation of presynaptic GABA receptors results in a transient (∼100 ms) enhancement of synaptic transmission (mediated by GABA(A) receptors) followed by a long lasting (>500 ms) inhibition of transmission (mediated by GABA(B) receptors). When activated just prior to high‐frequency trains of stimulation, presynaptic GABA(A) and GABA(B) receptors work together to reduce short‐term facilitation/enhance depression, altering the filtering properties of synaptic transmission. Inhibition of synaptic transmission by GABA(B) receptors is more sensitive to GABA than enhancement by GABA(A) receptors, suggesting GABA(B) receptors may be activated by ambient GABA or release from greater distances. ABSTRACT: GABA(A) and GABA(B) receptors are co‐expressed at many presynaptic terminals in the central nervous system. Previous studies have shown that GABA(A) receptors typically enhance vesicle release while GABA(B) receptors inhibit release. However, it is not clear how the competing actions of these receptors modulate synaptic transmission when co‐activated, as is likely in vivo. We investigated this question at parallel fibre synapses in the cerebellum, which co‐express presynaptic GABA(A) and GABA(B) receptors. In acute slices from C57BL/6 mice, we find that co‐activation of presynaptic GABA receptors by photolytic uncaging of RuBi‐GABA has a biphasic effect on EPSC amplitudes recorded from stellate cells. Synchronous and asynchronous EPSCs evoked within ∼100 ms of GABA uncaging were increased, while EPSCs evoked ∼300–600 ms after GABA uncaging were reduced compared to interleaved control sweeps. We confirmed these effects are presynaptic by measuring the paired‐pulse ratio, variance of EPSC amplitudes, and response probability. During trains of high‐frequency stimulation GABA(A) and GABA(B) receptors work together (rather than oppose one another) to reduce short‐term facilitation when GABA is uncaged just prior to the onset of stimulation. We also find that GABA(B) receptor‐mediated inhibition can be elicited by lower GABA concentrations than GABA(A) receptor‐mediated enhancement of EPSCs, suggesting GABA(B) receptors may be selectively activated by ambient GABA or release from more distance synapses. These data suggest that GABA, acting through both presynaptic GABA(A) and GABA(B) receptors, modulate the amplitude and short‐term plasticity of excitatory synapses, a result not possible from activation of either receptor type alone.